Security Economics: A Guide for Data Availability and Needs - Christos Kallandranis; Konstantinos Drakos (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
In this Policy Briefing, we review the available terrorism databases by focusing on their characteristics, advantages and disadvantages. This serves as a guide for policymakers and academic researchers alike. The rapid and accelerating development of security economics has generated great demand for more and better data, to accommodate the empirical research agenda. We also discuss data shortages and needs that are considered essential for enhancing our understanding of the complex phenomenon of terrorism, as well as designing and evaluating policy. We conclude that there is a need for terrorism related databases that will include more information, over and above terrorism incidents per se.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330